Early Malignant Melanoma Detection, Especially in Persons with Pigmented Skin. (February 2023) - Jicman, Paul Andrei; Smart, Hiske; Ayello, Elizabeth A.; Sibbald, R. Gary
Abstract : GENERAL PURPOSE: To present a comprehensive gap analysis of podiatric melanoma literature. TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this educational activity, the participant will:1. Select the appropriate assessment techniques for screening patients, especially those with skin of color, for melanoma.2. Compare and contrast the various types of melanoma.3. Discuss the results of the literature review that offer insight to clinicians screening patients for melanoma. ABSTRACT: Early detection of malignant melanoma is associated with better survival and clinical outcomes. Visual skin inspection is part of melanoma lesion assessment, but clinicians often have difficulty identifying lesions in persons with darker skin tones (eg, Fitzpatrick type 5 [brown] and type 6 [black] skin). There is also a lack of knowledge about the skin sites that are best to evaluate in persons with darkly pigmented skin (eg, the plantar surface of the feet, palms of the hand, and under the nail plate). These limitations can lead to a delay in diagnosis with potentially poor prognostic outcomes. In this article, the authors identify relevant literature to increase awareness for the presence of early signs of malignant melanoma in all skin types. Patient empowerment includes lifestyle adaptations, such as conducting regular skin and foot self-examinations to detect melanoma signs and applying sun protection on feet.